ASSESSMENT OF THE EFFICIENCY OF CELLULOSE MEMBRANES WITH CARBON ADSORBENT APPLICATION - Trembus, Iryna; Haponiuk, Anna (Science-based technologies, 2025)
The article focuses on the production of a filtration material from oxidative-organosolv cellulose derived from miscanthus, utilizing a carbon adsorbent for water purification from suspended particles causing turbidity. A methodology for modifying activated carbon with a potassium permanganate solution was proposed. Studies were conducted on the oxidation of carbon with KMnO₄ solutions at concentrations ranging from 0.015 to 0.035 meq/dm³, with durations between 15 and 135 minutes. Experimental results established that the deposition degree of MnO₂ on activated carbon ranges from 13% to 30%, depending on the modification duration and the initial KMnO₄ solution concentration. Regression equations were calculated, which adequately describe the experimental data and can be used as a mathematical model for the process of activated carbon oxidation. Using multicriteria optimization, compromise regions for conducting the carbon oxidation process were determined. A full factorial experiment established the optimal conditions for carbon treatment, corresponding to a duration of 55 minutes and a potassium permanganate solution concentration of 0.2 meq/dm³. As a result of the delignification process of miscanthus stems in the acetic acid–hydrogen peroxide–citric acid system, oxidative-organosolv cellulose was obtained with a yield of 62.4% and a residual lignin content of 1.84% based on the absolute dry weight of the raw material, along with high strength characteristics. The cellulose obtained was subsequently used as a base material for water purification membranes. The impact of using adsorptive material on the selectivity and productivity of cellulose filtration material was demonstrated. The addition of carbon adsorbent increases the productivity of membranes. It was determined that membranes made from modified cellulose fibers derived from miscanthus, containing adsorptive materials, are suitable for use in ultrafiltration processes.